Do Green Acquisitions Create Value? Evidence from US and Australian Markets - Soegiharto Soegiharto (STIE Tri Bhakti, 2026)
This study examines shareholder reactions to green mergers and acquisitions using 72 transactions by US and Australian acquirers during 2018–2020. The sample pairs 36 green acquisitions with 36 propensity-score-matched non-green deals, identified through textual screening and industry classification. Event-study methodology with a three-day window [?1, +1] and multiple robustness tests reveals that green acquisitions initially generate higher cumulative abnormal returns than non-green deals (2.85% versus 0.90%). However, cross-sectional regression shows that this green premium becomes statistically insignificant once traditional merger determinants—relative deal size, cross-industry diversification, and market-to-book ratios—are controlled for. These findings indicate that investors evaluate green acquisitions through conventional financial metrics rather than assigning systematic premiums to environmental attributes. The study contributes to the green M&A literature by demonstrating that deal fundamentals, not environmental positioning, drive market reactions during a period of heightened ESG policy focus, with implications for corporate environmental strategy and sustainable finance policy.